FAMILY EXPECTATIONS IN ELEMENTAL (2023) MOVIE - Achmalia Salma Putri; ., Ismiati (Conscientia - Journal on Language, Literature, and Culture, 2025)
This paper studies family expectations toward their child in the Elemental (2023) movie. Ember as the child is the main character in the film. Her parents consist of Bernie as the father, and Cinder as the mother. The objective of the study is to analyze what are the family expectations toward Ember. The data collection method applied is library research method focused on the scenes, dialogues, and character interactions in the film. The data analysis method employed is descriptive analysis, which aims to identify key themes related to family expectations. A psychological literary approach is used to examine the mental and emotional experiences of the characters. The theory applied in this study include Bowen’s Family Systems Theory, specifically the Family Projection Process stage. The findings show that there are three main family expectations passed down to Ember. First, Ember is expected to be able to continue the family business, which is the fire family shop, the Fireplace. Second, Ember is expected to preserve the family identity, like preserving fire family’s Blue flame, and marrying only fire element people. Third, Ember is expected to be able to control her temper. Those three family expectations have been transferred to Ember through nurturing, training, and preserving family tradition.